Pengaruh Kompetensi, Kompleksitas Tugas dan Skeptisme Profesional Terhadap Kualitas Audit pada Kantor Badan Pengawasan Keuangan dan pembangunan Provinsi Sumatera Utara - Deasy Arisandy Aruan; Hasrat Naeni Gulo; Ana Karelina Lumban Nahor; Natasya Br Ginting; Esti Trinita Wahyuni (Politeknik Ganesha Medan, 2019)
Audit quality is not easy to define because there are many factors that affect quality. This study aims to determine the effect of competence, task complexity, and Auditor Professional Skepticism, on Audit Quality. The data used in this study is primary data by distributing questionnaires to all auditors at the BPKP Representative Office in North Sumatra Province. The population in this study were all auditors at the BPKP Representative Office in North Sumatra Province. The collection of data and information needed in this study was carried out with field research. The data used are primary data collected directly from the research subjects with a questionnaire form. Testing the effect of independent variables on the dependent variable is done by using multiple regression models. The results of this study indicate that both partially and simultaneously, competence, task complexity, and Auditor Professional Skepticism, have an effect on Audit Quality in the BPKP Representative office in North Sumatra Province